PENGARUH PANDEMI COVID ??? 19 TERHADAP PENANAMAN NILAI-NILAI KARAKTER DALAM PEMBELAJARAN DARING SISWA SMA DI KABUPATEN TANGERANG - Neni Nuraeni Wiatiningsih (ISLAMIKA, 2023)
The learning process is the process of forging students which is done not only in the transfer of learning material but more importantly is the formation of student characters that are more related to the challenges involved. This discusses the character of planting so that students have good, independent, personal, and responsible character which is not only done for oneself but can also involve their personality and attitude towards others. Thus, the learning process provided by the teacher can be given completely. The teacher will respond well to students who have good personalities and characters.but during the covid ??? 19 pandemic it was all difficult to implemen.